Pembelajaran PPG Berbasis Technological Pedagogical And Content Knowledge (Tpack) Untuk Mewujudkan Guru Profesional - Darmawang, Darmawang; Rauf, Bakhrani; Zaki, Ahmad (Seminar Nasional LP2M UNM, 2024)
Arends, R. I. 2001. Learning to Teach. Fifth Edition. Singapore: McGraw-Hill Higher Education.Branch. 1999 dalam Akker, dkk. (editor). Design Approaches and Tools in Education and Training. Kluwer Academic Publisher. London.Chamberlin, M.T., Powers, R.A., & Novak, J.D. 2008. Teachers’ Perceptions of Mathematics Content Knowledge Assessments in Professional Development Courses. International Electronic Journal of Mathematics Education. Volume 3, Number 3Depdiknas. 2000. Pedoman Pelaksanaan Uji Coba Kurikulum Berbasis Kompetensi dan Pendidikan Berwawasan Khusus. Dir. Jend. Pend. Dasar dan Menengah, Jakarta.Harkness, W. L., Lane, J.L., & Harwood, J. T. 2003. A Cost-Effective Model for Teaching Elementary Statistics with Improved Student Performance. JALN. Vol. 7., Issue 2: 8-17.Hopkins, David. 2002. A Teacher's Guide to Classroom Research, third edition. Buckingham, UK: Open University Press.Howe, A. & Jones, L. 1993. Engaging children in science. New York: Macmillan Publishing Company.Hoy, W. K., & Miskel, C. G. 2005. Educational Administration (seventh ed.). New York: McGraw Hill.Ihsan, H. dkk. 2013. Pengembangan Model Pembelajaran Metode Kuantitatif e-learning Berbasis Kinerja Mahasiswa. Lemlit UNM Makassar.Ihsan, H. dkk. 2010-2013. Pengembangan Model Pembelajaran Matematika Berbasis Kinerja Mahasiswa. Lemlit UNM Makassar.Jan van den Akker. 1999. Principles and Methods of Development Research. Dalam Plomp, T; Nieven, N; Gustafson, K; Branch, R.M; dan van den Akker, J (eds). Design Approaches and Tools in Education and Training. London: Kluwer Academic Publisher.Joyce, B dan Weil, M. 1992. Models of Teaching. London: Prentice-Hall, Inc.Joyce, B., Weil, M., & Showers, B. 1992. Models of Teaching. Fourth Edition. Boston: Allyn & Bacon.Joyce, B., Weil, M., & Calhoun, C. 2009. Models of Teaching. Eighth Edition. Boston: Allyn & Bacon.Kemp, J.E. 1994. Proses Perancangan Pengajaran. Terjemahan oleh Asril Marjohan. Judul Asli The Instructional Design Process. Bandung: Penerbit ITB.NCTM. 2000. Principle and Standard for School Mathematics. Reston: The National Council of Teacher Mathematics, Inc. Nieveen, K. 1999. Prototyping to Reach Product Quality. Dalam Plomp, T; Nieveen, N; Gustafson, K; Branch, R.M; dan van den Akker, J (eds). Design Approaches and Tools in Education and Training. London: Kluwer Academic Publisher.Nieveen, N.M. & Akker, J.J.H., van den. 1999. Exploring the potential of a computer tool for instructional developers. Educational Technology Research & Development, 47(3), 77-98.Plomp, T. 1997. Educational and Training System Design. Enschede, The Netherlands: Univercity of Twente.Plomp, T. 1997. Educational Design: Introduction. From Tjeerd Plomp (eds). Educational & Training System Design: Introduction. Design of Education and Training (in Dutch). Utrecht (the Netherlands): Lemma. Netherland. Faculty of Educational Science and Technology, University of Twente.Plomp, T. & Nieveen, N. (editor). 2007. An Intriduction to Educational Design Research. Netzodruk, Enschede. Belanda.Polya, G. 1973. How To Solve It. Princeton: Princeton University Press.Solso, R.L. 1995. Cognitive Psychology. Boston: Allyn and Baccon.Thiagarajan, S., Semmel, D. S & Semmel, M. I. 1974. Instructional Development for Training Teachers of Expectional Children. Minneapolis, Minnesota: Leadership Training Institute/Special Education, University of Minnesota.